2022
DOI: 10.1002/adom.202200230
|View full text |Cite
|
Sign up to set email alerts
|

The Tuning of Exciton‐Phonon Coupling in Colloidal Nanocrystals by a Dielectric Medium

Abstract: Here, a thorough study is reported that exposes the influence of surfactants’ dielectric screening on the exciton energy and exciton‐phonon coupling in CdSe and CdSe/CdS colloidal quantum dots and nanoplatelets. The study follows the temperature dependence of the photoluminescence spectrum to monitor thermally activated exciton‐phonon interactions. The dependence of the exciton energy on temperature exhibits an anomalous point at ≈250 K, which coincides with the melting point of surfactant ligands (oleate mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The results of narrowed FWHM of LO peak and decreased 2LO/LO intensity ratio also indicate the weakening of exciton-LO phonon coupling. [50][51][52] Therefore, the reduced FWHM in ZnSeTe/ZnSe/ZnS QDs is considered to mainly come from a decrease of homogeneous broadening contribution due to weakened exciton-LO phonon coupling and combine with the suppression of trap emissions with a coating of internal ZnSe shell.…”
Section: Exciton-lo Phonon Coupling and Carrier Trapping Process Disc...mentioning
confidence: 99%
“…The results of narrowed FWHM of LO peak and decreased 2LO/LO intensity ratio also indicate the weakening of exciton-LO phonon coupling. [50][51][52] Therefore, the reduced FWHM in ZnSeTe/ZnSe/ZnS QDs is considered to mainly come from a decrease of homogeneous broadening contribution due to weakened exciton-LO phonon coupling and combine with the suppression of trap emissions with a coating of internal ZnSe shell.…”
Section: Exciton-lo Phonon Coupling and Carrier Trapping Process Disc...mentioning
confidence: 99%
“…Colloidal chemistry has been long used for obtaining nanostructures of metal chalcogenides in the form of dots, , wires, sheets, platelets, , and many more. Additionally, the growth of the colloidal metal chalcogenides into various branched nanostructures (BNSs) has also been observed, many times serendipitously.…”
mentioning
confidence: 99%
“…However, recent studies on PbS, PbSe, CdS, and CdSe NCs prepared via hot injection have shown that the nucleation phase sometimes overlaps significantly with the growth phase due to extended nucleation and the size-dependent growth leads to narrow size distribution. 3−5 Colloidal chemistry has been long used for obtaining nanostructures of metal chalcogenides in the form of dots, 6,7 wires, 8 sheets, 9 platelets, 10,11 and many more. Additionally, the growth of the colloidal metal chalcogenides into various branched nanostructures (BNSs) has also been observed, 12−16 many times serendipitously.…”
mentioning
confidence: 99%